Finding of nevirapine extended release tablet remnants in stools does not threaten the success of combination antiretroviral therapy. Issue 2 (23rd September 2013) - Stephan, C; León, W
<x xml:space="preserve">Abstract</x> Objectives The finding of nevirapine extended release (XR) tablet remnants in stools has raised concerns about emerging HIV‐1 resistance. The aim of this study was to evaluate the characteristics and pharmacokinetic and virological outcomes of affected patients from clinical trials. Methods HIV‐1‐infected individuals reporting tablet remnants in stools during phase III (VERxVE and TRANxITION‐studies)‐clinical trials were evaluated for mean pharmacokinetic nevirapine concentrations in available blood trough samples and remnants from stool. Patient characteristics including age, race, geographical region and primary study endpoint outcome were investigated for risk factor association with the finding of tablet remnants. Results Of 800 patients receiving the nevirapine XR formulation, 15 reported tablet remnants in stools, an incidence rate of 1.19% in VERxVE and 3.05% in the TRANxITION study. The difference in event rate was highly significant between the XR and immediate release (IR) formulations (P < 0.001), but not between trials (P = 0.061). All patients (15 of 15) reporting remnants achieved the primary study endpoint of HIV‐1 suppression (< 50 HIV‐1 RNA copies/mL), whereas overall 81% of patients in the VERxVE trial and 94% in the TRANxITION trial did so. The mean nevirapine trough concentration was 3431.4 ng/mL in patients reporting remnants. Tablet remnants retrieved from the stools of three subjects revealed a percentage nevirapine recovery of 22.8–42.2% of original drug. Subgroup analysis of gender, age, race and geographical region revealed no risk factor association with the finding of remnants. Conclusions The finding of nevirapine tablet remnants in stools is a rare event, with an incidence of approximately 2%, restricted to the XR formulation. Affected patients responded fully to antiretroviral therapy by achieving the primary study endpoint and demonstrating no relevant safety risks; nevirapine pharmacokinetic analysis of blood and stool samples ruled out underexposure.